Molybdoenzymes and molybdenum cofactor in dormant and developing wheat seeds (Experimental biology, 2016)
The distribution of the activities of molybdenum соfасtor (МоСо) and molybdenum containing enzymes - nitrate reductase (NR), aldehyde oxidase (АО) and xanthine dеhуdrоgеnаsе (XDH) in different parts of dormant and developing wheat seeds are studied. The activities of МоСо, АО and XDH were highest in the embryo. The aleurone layer of the seed also showed these activities; however, activity levels in the aleurone were approximately three times lower than those in the embryo. The activities of these molybdoenzymes were not detected in the endosperm portion of the seed. There was no detectable NR activity in any part of the seed. The XDH activity remained at a steady level in both the embryo and endosperm throughout the course of seed development and maturation, whereas АО activity was extremely low in these same seed parts. However, АО activity increased at a high rate when seeds entered desiccation phase. At this stage, the content of ureides also increased by two and a half times. It is known that AO is involved in abscisic acid (ABA) biosynthesis, converting abscisic aldehyde to ABA, and the by-product of this reaction is superoxide. Therefore, we propose that increased ABA synthesis results in the increase of reactive oxygen species (ROS), which are scavenged by uric acid forming ureides.Тыныштық күй мен даму сатысындағы бидай дәндерінің түрлі бөліктерінде молибденді кофакторлар (Мо-со) мен молибденді ферменттер: нитрат редуктаза (НР), альдегидоксидаза(АО) мен ксантиндегидрогенезаның(КДГ) таралуы зерттелді. МоСо, АО мен КДГ жоғары белсенділікте ұрықта анықталды. Ұрық бөліміне қарағанда алейронды қабатта осы ферменттер мен МоСо белсенділігі үш есе төмен болды. Дәннің эндоспермдік бөлімінде бұл ферменттердің белсенділігі тіркелмеді. НР белсенділігі дәннің ешқандай бөлігінде анықталмады. КДГ белсенділігі даму және жетілу кезеңдерінде ұрық бөлімінде де, эндосперм бөлігінде де бірдей болып сақталса, ал АО белсенділігі аталған бөліктерде экстрималды төмен деңгейде анықталды. Алайда, АО дән дегидратация фазасы кезінде көптеген ылғалды жоғалтқан жағдайда жоғары жылдамдықпен артты. Осы фазада уреидтер де 2,5 есе артты. АО абсциз альдегидін АБҚ-на дейін өзгертіп, АБҚ биосинтезіне қатысатындығы және осы реакция өнімі супероксид екендігі белгілі. Сондықтан да, біз АБҚ-ның жоғары биосинтезі несеп қышқылы арқылы бейтараптанып, уреид түзетін оттегінің реактивті радикалдарының пайда болуына алып келеді деп болжаймыз. Изучены распределение молибденового кофактора( Мо-со) и активностей молибден содержащих ферментов - нитрат редуктазы (НР), альдегид оксидазы (AО) и ксантиндегидрогеназы ( КДГ) в различных частях покоящегося и созревающегося зерна пшеницы. Были показаны наиболее высокие активности МоСо, АО и КДГ - в зародыше. В три раза меньше уровень активности этих же ферментов и Мосо наблюдался в алейроновом слое, чем в зародыше. Активности этих ферментов не обнаруживались в эндоспермальной части семени. Активность НР не обнаруживалась ни в одной части зерна. Активность КДГ оставалась равномерной как в зародыше, так и в эндосперме в течение периода развития и созревания , тогда как активность АО была экстремально низкой в этих частях зерна. Однако активность АО увеличилась с высокой скоростью когда зерновка теряла влажность во время фазы дегидратации. В этой фазе содержание уреидов также увеличивалось в 2,5 раза. Известно, что АО вовлечен в биосинтез АБК, превращая абсцизовый альдегид до АБК, и супероксид становится продуктом этой реакции. Поэтому, мы предполагаем, что повышенный биосинтез АБК приводит к увеличению реактивных радикалов кислорода, которые нейтрализуются с помощью мочевой кислоты образуя уреиды.
Keywords: Aldehyde oxidase; dormancy; molybdoenzymes; molybdenum cofactor; nitrate reductase; wheat seeds; xanthine dehydrogenase.